Injuries and molting interference in a trilobite from the Cambrian (Furongian) of South China - Ruiwen Zong (PeerJ, 2021)
An injured Shergoldia laevigata Zhu, Hughes & Peng, 2007 (Trilobita, Asaphida) was collected from the Furongian of Guangxi, South China. The injuries occurred in the left thoracic pleurae possessing two marked V-shaped gaps. It led to substantial transverse shortening of the left pleural segments, with barely perceptible traces of healing. This malformation is interpreted as a sub-lethal attack from an unknown predator. The morphology of injuries and the spatial and temporal distribution of predators indicated that the predatory structure might have been the spines on the ganathobase or ganathobase-like structure of a larger arthropod. There were overlapped segments located in the front of the injuries, and slightly dislocated thoracic segments on the left part of the thorax, suggesting that the trilobite had experienced difficulties during molting. The freshly molted trilobite had dragged forward the old exuvia causing the irregular arrangement of segments. This unusual trilobite specimen indicates that the injuries interfered with molting.